High-frequency electric welding of biological tissues versus diode laser photocoagulation as intraoperative retinopexy in vitrectomy for rhegmatogenous retinal detachment N.N. Umanets, Cand Sc (Med) - N.N. Umanets (Ukrainian Society of Ophthalmologists, 2016)
Background: It is important to find an alternative retinopexy technique allowing for the exclusion of silicone oil (or gas) tamponade of the vitreous cavity from the vitrectomy procedure for rhegmatogenous retinal detachment (RRD). Materials and Methods: A retrospective non-randomized study was conducted and included 112 patients (112 eyes) with uncomplicated RRD. Retinopexy in the study group (53 patients, 53 eyes) and in controls (59 patients, 59 eyes) was performed using high-frequency electric welding of biological tissues (HFEWBT) and 810-nm laser irradiation, respectively. Results: Mean visual acuity increased to higher levels in the HFEWBT group than in controls at 2 months (0.29 versus 0.21, P = 0.035; this is due to the fact that we managed to avoid intraoperative tamponade in 30% of patients of the study group, thus enabling maintenance of clarity of the posterior lens capsule) and 12 months (0.41 versus 0.39, P > 0.05). Conclusions: High-frequency electric welding of biological tissues (a) is a safe and efficient method for obtaining a firm chorioretinal adhesion, (b) can be used in the clinical practice for intraoperative retinopexy at the time of vitrectomy in patients with uncomplicated RRD, and (c) can ensure retinal re-attachment at the long-term follow-up in as much as 96% of such cases.